Effect of Dopant Concentration on Wet Chemical Grown Zn1-xMnxS Nanoparticles - Elango, M.; Gopalakrishnan, K.; Prem Nazeer, K.; Thamilselvan, M. (Current Nanoscience, 2012)
Nanodimensional Zn1-xMnxS particles were synthesized with x=5, 10 and 15 wt % of Mn2+ ions by wet chemical method. Synthesized Zn1-xMnxS nanoparticles were characterized with X-ray diffraction (XRD) method, High resolution transmission electron microscopic (HRTEM) analysis, UV-Visible absorption spectroscopic method, Fourier transform infrared (FT-IR) analysis and vibrating sample magnetometer method. The XRD analysis showed that upon increasing the dopant concentration from 10% to 15%, hexagonal wurtzite phase changed into cubic zinc blende structure and it was originated by large level replacement of Zn2+ with Mn2+. HRTEM analysis confirmed the nanophase formation with partial mono dispersity and less amalgamation of particles. Blue shift was observed in UVVisible spectra which further established the reduced particle size (30 nm) and its subsequent increase in bandgap was estimated. The strong Mn-S and weak Zn-S interactions were indentified from FT-IR analysis. The superparamagnetism was inferred from VSM analysis for the samples of three doping concentrations, and further, alteration in the aligned paramagnetic grains with respect to the applied field was also indentified for heavily doped sample.
Keywords: optical studies